BERAKHIRNYA KONTRAK PERSPEKTIF HUKUM PERDATA - Muthia Savitri, Muhammad Silmi; Ukas, Ukas (LPPM Universitas Putera Batam, 2024)
Nowadays there are many conflicts or problems that often occur in a contract agreement, the agreement inquestion is a contractual agreement made by legal subjects in the interest of civil law, in the end of anagreement there are a lot of problems nowadays that arise because many legal subject parties who enter intoan agreement do not understand the procedures for terminating an agreement. This causes a lot of losses toarise for one of the parties and as a result, the party who feels disadvantaged takes legal action. A very bigproblem for the parties involved. at a loss in an agreement, many of the parties terminate or terminate theagreement in bad faith and will cause conflict. It is very unfortunate that the problem of this agreement cannotbe resolved properly by the parties, such as in a contract agreement where the contract is a very authenticagreement, usually when making work contracts and contacts, for example, it is made by people whounderstand the making of such contracts and there is very little if any conflict occurs. However, nowadayscontracts are often problematic even though they are made by competent people, but it is still problematic whythis can happen, of course this happens because in making a contract, there is an agreement that must beprioritized by the parties and also regulates regarding how to end the contract, and also the good faith of theparties if they wish to terminate or end the contract